Le protesi di capitello radiale - Butera, M.; La Gattuta, A.; Siragusa, F.; Abruzzese, A.; Valenti, G.D.; Zini, S.; Colaiuda, F. (Lo Scalpello - Journal, 2019)
RADIAL HEAD PROSTHESIS Radial head prosthesis has been developed to reduce potential complications resulting from radial head resection surgery. Principal indications are for not fixable fractures associated with lesions of the other stabilisers (coronoid, olecranon, LCM, LCL, interosseous membrane). Starting from the first models, these prostheses have undergone considerable changes both as regards materials and as regards types. Although today prosthetic replacement of the radial capital is considered as a valid option in the treatment of comminuted fractures, it is evident, however, that even this type of treatment may not be free from complications.